Religiosity Mediates the Influence of Entrepreneurial Orientation and Digital Financial Literacy on The Performance of Kudus District MSMEs - Hamidah; Buchdadi, Agung Dharmawan; Pebianti, Vina; Suprayogi, Wahyu; Prameswari, Rita (Journal of Business and Behavioural Entrepreneurship, 2024)
This research aims to examine the role of religiosity in mediating the influence of entrepreneurial orientation and digital financial literacy on the performance of MSMEs. This research method uses quantitative methods. The object of this research was the UMKM Embroidery, Convection and Batik Cluster in Kudus Regency, Central Java. By using primary data sources by distributing questionnaires to MSME players, the collected data is then processed using the alternative partial least squares (PLS) structural equation modeling (SEM) method with the smartPLS program. The results of the research indicate that 1) Entrepreneurial Orientation does not affect Performance, 2) Financial Digital Literacy affects Performance, 3) Religiosity affects Performance, 4) Entrepreneurial Orientation affects Religiosity, 5) Financial Digital Literacy affects Religiosity, 6) Entrepreneurial Orientation does not affect Performance through Religiosity, and 7) Financial Digital Literacy affects Performance through Religiosity.